Polymorphisms of suppressor of cytokine signaling-3 associated with susceptibility to tuberculosis among Han Taiwanese. (February 2019) - Lin, Chou-Jui; Lee, Shih-Wei; Liu, Chi-Wei; Chuu, Chih-Pin; Kao, Yung-Hsi; Wu, Lawrence Shih-Hsin
Abstract: Background: Suppressors of cytokine signaling (SOCS), particularly SOCS-3, allow discrimination of patients with active tuberculosis (TB) from healthy subjects in a gender- and age-dependent manner. However, no information is available on whether single nucleotide polymorphisms (SNPs) in the SOCS-3 gene occur in patients with TB. This study was designed to investigate SOCS-3 SNPs in association with susceptibility to TB in the Taiwanese population. Methods: Four SNPs in the SOCS-3 gene located at rs8064821, rs4969168, rs2280148, and rs35037722 were studied by the TaqMan SNP Genotyping assay in 200 healthy and 210 TB patients enrolled in 2015–2018. Results: Significant differences were not detected in genotype frequencies or odds ratios (ORs) between healthy and TB patients for any of the four polymorphisms. The lack of significant differences was also found when the patients were stratified by sex. However, males exhibited GG homozygous at rs35037722 in association with susceptibility to TB after the OR analysis was adjusted for age. For rs8064821, AA and AC genotypes were associated with TB susceptibility in patients ≤ 65 years old compared to CC genotype, whereas older subjects had no such association. Conclusions: The results suggest that particular SOCS-3 SNPs are dependent on gender or age to influence TB susceptibility in the Han Taiwanese.